A STATE-OF-THE-ART REVIEW OF THE REAL-TIME COMPUTER-AIDED STUDY OF THE WRITING PROCESS - Abdel Latif, Muhammad M. (International Journal of English Studies, 2008)
Writing researchers have developed various methods for investigating the writing process since the 1970s. The early 1980s saw the occurrence of the real-time computer-aided study of the writing process that relies on the protocols generated by recording the computer screen activities as writers compose using the word processor. This article reviews literature on that approach to studying the writing process. The article begins with defining the realtime computer-aided study of the writing process, tracing its historical development, and explaining the advantages it offers, then it gives a brief description of the software that has been used in the computer-aided writing process research and discusses the ways of analyzing the logged data, and it ends with overviewing the computer-aided writing process research.